Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

Tide–surge interaction observed at Singapore and the east coast of Peninsular Malaysia using a semi-empirical model - Zhi Yang Koh; Benjamin S. Grandey; Dhrubajyoti Samanta; Adam D. Switzer; Benjamin P. Horton; Justin Dauwels; Lock Yue Chew (Ocean Science, 2024)
Tide–surge interaction plays a substantial role in determining the characteristics of coastal water levels over shallow regions. We study the tide–surge interaction observed at seven tide gauges along Singapore and the east coast of Peninsular Malaysia, focusing on the timing of extreme non-tidal residuals relative to tidal high water. We propose a modified statistical framework using a no-tide–surge interaction (no-TSI) null distribution that accounts for asymmetry and variation in the duration of tidal cycles. We find that our modified framework can mitigate false-positive signals of tide–surge interaction in this region. We find evidence of tide–surge interaction at all seven locations, with characteristics varying smoothly along the coastline: the highest non-tidal residuals are found to occur most frequently before tidal high water in the south, both before and after tidal high water in the central region, and after tidal high water in the north. We also propose a semi-empirical model to investigate the effects of tidal-phase alteration, which is one mechanism of tide–surge interaction. Results of our semi-empirical model reveal that tidal-phase alteration caused by storm surges is substantial enough to generate significant change in the timing of extreme non-tidal residuals. To mitigate the effect of tidal-phase alteration on return level estimation, skew surge can be used. We conclude that (1) tide–surge interaction influences coastal water levels in this region, (2) our semi-empirical model provides insight into the mechanism of tidal-phase alteration, and (3) our no-TSI distribution should be used for similar studies globally.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Representation of Boundary-Layer Processes in Numerical Weather Prediction and Climate Models - John M. Edwards; Anton C. M. Beljaars; Albert A. M. Holtslag; Adrian P. Lock (Boundary-Layer Meteorology, 2020)

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.

Correction to: Defining the role of cytoskeletal components in the formation of apoptopodia and apoptotic bodies during apoptosis - Sarah Caruso; Georgia K. Atkin‑Smith; Amy A. Baxter; Rochelle Tixeira; Lanzhou Jiang; Dilara C. Ozkocak; Jascinta P. Santavanond; Mark D. Hulett; Peter Lock; Thanh Kha Phan; Ivan K. H. Poon (Apoptosis, 2019)

Defining the role of cytoskeletal components in the formation of apoptopodia and apoptotic bodies during apoptosis - Sarah Caruso; Georgia K. Atkin-Smith; Amy A. Baxter; Rochelle Tixeira; Lanzhou Jiang; Dilara C. Ozkocak; Jascinta P. Santavanond; Mark D. Hulett; Peter Lock; Thanh Kha Phan; Ivan K. H. Poon (Apoptosis, 2019)

Mineral nutrition and bone health in salmonids - Grete Baeverfjord; P. Antony Jesu Prabhu; Per Gunnar Fjelldal; Sissel Albrektsen; Bjarne Hatlen; Vegard Denstadli; Elisabeth Ytteborg; Harald Takle; Erik‐Jan Lock; Marc H.G. Berntssen; Anne‐Katrine Lundebye; Torbjørn Åsgård; et al. (Reviews in Aquaculture, 2019)
In the recent years, challenges faced in salmonid farming with regard to deformities have helped to improve our knowledge on skeletal biology and development of bone health in salmonids. Different nutritional, genetic and environmental factors are associated with skeletal deformities in salmonids and other fish species. Minerals are a group of essential nutrients having a vital role to play in skeletal development, growth and remodelling. The knowledge generated thus far on the structural and functional importance of minerals in salmonid bone health is largely restricted to phosphorus. A brief account of dietary phosphorus‐related bone deformities encountered in salmonids, critical life stages for the development of bone deformities, recent developments in the understanding of their aetiology and dietary phosphorus levels required to improve bone health are presented. The effect of increased dietary level of phosphorus in reducing bone health disorders under conditions of improved feed conversion efficiency and use of triploids in salmon farming are illustrated with help of metadata analysis from literature. With regard to the role of other essential minerals (macro‐ and micro‐) impacting bone health in salmonids, data available are extremely limited and hence information on other fish species and mammals is summarized in relation to bone development and incidence of deformities. The need to improve mineral bioavailability, utilization and reduce effluent mineral load is presented in brief with example from Norwegian salmon farming. Refinements in mineral requirement recommendations for salmonids and advanced methodologies for studying aetiology of skeletal anomalies, bone mineral status, skeletal development and deformities are also discussed.

Drought timing, not previous drought exposure, determines sensitivity of two shortgrass species to water stress - Nathan P. Lemoine; Robert J. Griffin-Nolan; Abigail D. Lock; Alan K. Knapp (Oecologia, 2018)

NESSCA Validation and Responsiveness of Several Rating Scales in Spinocerebellar Ataxia Type 2 - Thais L. Monte; Estela R. Reckziegel; Marina C. Augustin; Amanda S. P. Silva; Lucas D. Locks-Coelho; Orlando Barsottini; José L. Pedroso; Fernando R. Vargas; Maria-Luiza Saraiva-Pereira; Vanessa Bielefeldt Leotti; Laura Bannach Jardim (The Cerebellum, 2017)

Inter-laboratory study of human in vitro toxicogenomics-based tests as alternative methods for evaluating chemical carcinogenicity: a bioinformatics perspective - R. Herwig; H. Gmuender; R. Corvi; K. M. Bloch; A. Brandenburg; J. Castell; L. Ceelen; C. Chesne; T. Y. Doktorova; D. Jennen; P. Jennings; A. Limonciel; et al. (Archives of Toxicology, 2016)

ATXN3, ATXN7, CACNA1A, and RAI1 Genes and Mitochondrial Polymorphism A10398G Did Not Modify Age at Onset in Spinocerebellar Ataxia Type 2 Patients from South America - Fernanda S. Pereira; Thais L. Monte; Lucas D. Locks-Coelho; Amanda S. P. Silva; Orlando Barsottini; José L. Pedroso; Mario Cornejo-Olivas; Pilar Mazzetti; Clecio Godeiro; Fernando R. Vargas; Maria-Angélica F. D. Lima; Hélio van der Linden; et al. (The Cerebellum, 2015)

The diurnal cycle of marine cloud feedback in climate models - Mark J. Webb; Adrian P. Lock; Alejandro Bodas-Salcedo; Sandrine Bony; Jason N. S. Cole; Tsuyoshi Koshiro; Hideaki Kawai; Carlo Lacagnina; Frank M. Selten; Romain Roehrig; Bjorn Stevens (Climate Dynamics, 2015)

Maladaptation and phenotypic mismatch in hatchery‐reared Atlantic salmon Salmo salar released in the wild - R. Stringwell; A. Lock; C. J. Stutchbury; E. Baggett; J. Taylor; P. J. Gough; C. Garcia de Leaniz (Journal of Fish Biology, 2014)
Changes in body shape, fluctuating asymmetry ( FA ) and crypsis were compared among Atlantic salmon Salmo salar fry kept as controls in captivity and those released and subsequently recaptured in the wild according to a before‐after‐control‐impact ( BACI ) design. Hatchery fish that survived in the wild became more cryptic and displayed a much lower incidence of fin erosion and of asymmetric individuals than control fish kept in captivity. Significant differences in body shape were also apparent, and survivors had longer heads, thicker caudal peduncles and a more streamlined body shape than hatchery controls as early as 20 days following stocking, most likely as a result of phenotypic plasticity and non‐random, selective mortality of maladapted phenotypes. Hatchery‐reared fish typically perform poorly in the wild and the results of this study indicate that this may be due to phenotypic mismatch, i.e. because hatcheries generate fish that are phenotypically mismatched to the natural environment.

Coupling between subtropical cloud feedback and the local hydrological cycle in a climate model - Mark. J. Webb; Adrian P. Lock (Climate Dynamics, 2013)

Oxidative stress induced by potassium bromate exposure results in altered tight junction protein expression in renal proximal tubule cells - Alice Limonciel; Anja Wilmes; Lydia Aschauer; Robert Radford; Katarzyna M. Bloch; Tara McMorrow; Walter Pfaller; Joost H. van Delft; Craig Slattery; Michael P. Ryan; Edward A. Lock; Paul Jennings (Archives of Toxicology, 2012)

Transcriptomic alterations induced by Ochratoxin A in rat and human renal proximal tubular in vitro models and comparison to a rat in vivo model - Paul Jennings; Christina Weiland; Alice Limonciel; Katarzyna M. Bloch; Robert Radford; Lydia Aschauer; Tara McMorrow; Anja Wilmes; Walter Pfaller; Hans J. Ahr; Craig Slattery; Edward A. Lock; et al. (Archives of Toxicology, 2012)

Dietary fatty acids and inflammation in the vertebral column of Atlantic salmon, Salmo salar L., smolts: a possible link to spinal deformities - L Gil Martens; E J Lock; P G Fjelldal; A Wargelius; P Araujo; B E Torstensen; P E Witten; T Hansen; R Waagbø; R Ørnsrud (Journal of Fish Diseases, 2010)
Vegetable oils (Vo) are an alternative to fish oil (Fo) in aquaculture feeds. This study aimed to evaluate the effect of dietary soybean oil (Vo diet), rich in linoleic acid, and of dietary fish oil (Fo diet) on the development of spinal deformities under bacterial lipopolysaccharide (LPS)‐induced chronic inflammation conditions in Atlantic salmon, Salmo salar L. Fish [25 g body weight (BW)] were fed the experimental diets for 99 days. On day 47 of feeding (40 g BW), fish were subjected to four experimental regimes: (i) intramuscular injections with LPS, (ii) sham‐injected phosphate‐buffered saline (PBS), (iii) intraperitoneally injected commercial oil adjuvant vaccine, or (iv) no treatment. The fish continued under a common feeding regime in sea water for 165 more days. Body weight was temporarily higher in the Vo group than in the Fo group prior to immunization and was also affected by the type of immunization. At the end of the trial, no differences were seen between the dietary groups. The overall prevalence of spinal deformities was approximately 14% at the end of the experiment. The Vo diet affected vertebral shape but did not induce spinal deformities. In groups injected with LPS and PBS, spinal deformities ranged between 21% and 38%, diet independent. Deformed vertebrae were located at or in proximity to the injection point. Assessment of inflammatory markers revealed high levels of plasma prostaglandin E 2 (PGE 2 ) in the Vo‐fed and LPS‐injected groups, suggesting an inflammatory response to LPS. Cyclooxigenase 2 (COX‐2) mRNA expression in bone was higher in fish fed Fo compared to Vo‐fed fish. Gene expression of immunoglobulin M (IgM) was up‐regulated in bone of all LPS‐injected groups irrespective of dietary oil. In conclusion, the study suggests that Vo is not a risk factor for the development of inflammation‐related spinal deformities. At the same time, we found evidence that localized injection‐related processes could trigger the development of vertebral body malformations.

Upgrades to the Boundary-Layer Scheme in the Met Office Numerical Weather Prediction Model - A. R. Brown; R. J. Beare; J. M. Edwards; A. P. Lock; S. J. Keogh; S. F. Milton; D. N. Walters (Boundary-Layer Meteorology, 2008)

Effects of Mining Activities on Heavy Metal Concentrations in Water, Sediment, and Macroinvertebrates in Different Reaches of the Pilcomayo River, South America - A. J. P. Smolders; R. A. C. Lock; G. Van der Velde; R. I. Medina Hoyos; J. G. M. Roelofs (Archives of Environmental Contamination and Toxicology, 2003)

The role of glutathione S-transferase- and cytochrome P450-dependent metabolism in the olfactory toxicity of methyl iodide in the rat - M. P. Chamberlain; E. A. Lock; B. A. Gaskell; C. J. Reed (Archives of Toxicology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)